From gerontology to geroscience: a synopsis on ageing - Chmielewski, Piotr Paweł (Anthropological Review, 2020)
Biological ageing can be tentatively defined as an intrinsic and inevitable degradation of biological function that accumulates over time at every level of biological organisation from molecules to populations. Senescence is characterised by a progressive loss of physiological integrity, leading to impaired function and increased vulnerability to death. With advancing age, all components of the human body undergo these cumulative, universal, progressive, intrinsic and deleterious (CUPID) changes. Although ageing is not a disease per se, age is the main risk factor for the development of a panoply of age-related diseases. From a mechanistic perspective, a myriad of molecular processes and components of ageing can be studied. Some of them seem especially important and they are referred to as the hallmarks of ageing. There is compelling evidence that senescence has evolved as an emergent metaphenomenon that originates in the difficulty in maintaining homeodynamics in biological systems. From an evolutionary perspective, senescence is the inevitable outcome of an evolutionarily derived equilibrium between the amount of resources devoted to somatic maintenance and the amount of resources devoted to sexual reproduction. Single-target, single-molecule and disease-oriented approaches to ageing are severely limited because they neglect the dynamic, interactive and networking nature of life. These limitations notwithstanding, many authors promote single-target and disease-oriented approaches to senescence, e.g. repurposed drugs, claiming that these methods can enhance human health and longevity. Senescence is neither a disease nor a monolithic process. In this review, the limitations of these methods are discussed. The current state of biogerontology is also summarised.